Technique, Indications and Limitations of a Minimally Invasive Approach to Treat Distal Radius Fractures and Malunions - Liverneaux, Philippe; Amiri, Laela El; Facca, Sybille; Sapa, Marie-Cécile (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2023)
The minimally invasive flexor carpi radialis approach can be used for volar locking plate fixation of distal radius fractures. It offers the advantage of preserving ligamentotaxis, which facilitates the reduction and the small size of the scar improves the esthetic result of the procedure. It is indicated for extra-articular fractures of the distal radius. In the case of an intra-articular fracture, an arthroscopy may be associated. In the case of a proximal diaphyseal extension of the fracture, a second proximal approach can be added in order to use a longer plate. Relative contraindications are comminuted articular fractures in elderly osteoporotic patients. Functional and radiological results are comparable to those obtained with the extented flexor carpi radialis approach. A conversion of the procedure for a larger incision is always possible in the case of a difficult reduction.
Keywords: fractures; MIPO; distal radius; minimally invasive; extended FCR approach; minimally invasive FCR approach